Molecular typing of Burkholderia cepacia complex isolated from patients attending an Italian Cystic Fibrosis Centre - Teri, Antonio; Sottotetti, Samantha; Biffi, Arianna; Girelli, Daniela; D'Accico, Monica; Arghittu, Milena; Colombo, Carla; Corti, Fabiola; Pizzamiglio, Giovanna; Cariani, Lisa (The New microbiologica, 2018)
Bacteria from the Burkholderia cepacia complex (Bcc) are capable of causing severe infections in patients with cystic fibrosis (CF). Bcc infection is often extremely difficult to treat due to its intrinsic resistance to multiple antibiotics. In addition, it seems to speed up the decline of lung function and is considered a contraindication for lung transplantation in CF. This study investigates the species of the Bcc strains recovered from chronically infected CF subjects by means of: isolation, identification methods and complete recA nucleotide sequences of 151 samples. Molecular typing showed that B. cenocepacia III is the dominant strain found in the group of subjects being treated at the Milan CF Centre (Italy) and that the infection is chronically maintained by the same species. Defining species by means of molecular analysis yields important information for the clinician in order to establish the most appropriate therapy and implement correct measures for prevention of transmission among CF subjects.